Pengaruh Puasa Ramadhan terhadap Kadar Gula Darah pada Pasien Diabetes Mellitus Tipe II - Riandi Alfin; Busjra Busjra; Rohman Azzam (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effect of Ramadan fasting on blood sugar levels in diabetics in Purwakarta City Health Center, West Java. The research design used a quasi-experimental pre and post test with control group. The results of this study using the T-Independent test of fasting differences in blood sugar levels after Ramadan fasting in the control group and the intervention group obtained p value = 0.039 <α = 0.05. This means that the results of this study indicate the effect of Ramadan fasting on blood sugar levels in patients with type II diabetes mellitus at Puskesmas Kota Purwakarta. In conclusion, carrying out fasting in the month of Ramadan can be used as an alternative diet method that has positive benefits if it is carried out by people with type II diabetes mellitus, which can lower blood sugar to make it more stable. Keywords: Type II Diabetes Mellitus, Blood Sugar Levels, Ramadan Fasting